Analysis of Determinants of Compliance in Paying Land and Building Tax (PBB) Based on Maqasid Sharia in Langkat - Malahayati Malahayati; Yenni Samri Juliati Nasution; Maryam Batubara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The study explains the problems regarding public compliance in paying land and building taxes based on Maqasid Sharia in Langkat Regency. Therefore, this study aims to analyze the effect of motivation, income, education level, and socialization on compliance with paying property tax based on Maqasid Sharia. This research uses a descriptive approach with the type of literature study research and the analysis technique used is the Miles and Huberman model analysis technique. The results showed that the people in Langkat Regency, especially in Pematang Tengah Village, had a low level of awareness of paying land and building tax, a low level of public compliance with land and building tax, no sanctions against people who did not pay taxes,